LITERATUR REVIEW: TERAPI GEN SEBAGAI ALTERNATIF PENGOBATAN PENYAKIT KANKER - Hana E Yuliani; Windi P Firdhiana, Selfi A Ningrum, Titis D Vira, Nurce Khasanah, Atip Nurwahyunani, Endah Rita Suli (CV. ADIBA AISHA AMIRA, 2024)
Cancer has become one of the global health challenges that require innovative and effective solutions. Gene therapy has shown significant potential as a promising alternative in addressing cancer, transforming the traditional treatment paradigm that is limited. The goal of this article is to thoroughly examine the role of gene therapy as an alternative cancer treatment. The methods employed include a literature study with data analysis using qualitative content. More than 23 articles from 2012 to 2023 were used as literature sources. The research results indicate that the genetic engineering process in gene therapy technology includes the following steps: isolating the target gene, inserting the target gene into a transfer vector, transferring the insertion vector containing the target gene into the body requiring treatment, and transforming cells from the target organism. The target gene inserted into the body for treatment will be able to replace the function of abnormal disease- causing genes in patients. Another implementation of gene therapy in cancer treatment involves tumor suppressor genes, such as p53. Gene therapy has been used in cancer treatment for quite some time, including CAR-T gene therapy. CAR-T stands for chimeric antigen receptor T-cell therapy, where T cells are extracted from the patient and then genetically modified to recognize cancer cells, returning the modified T cells to the patient's body.